THE DEVELOPMENT OF SCIENTIFIC-BASED E-MODULES TO IMPROVE CONCEPTUAL UNDERSTANDING OF NUTRITION STUDENTS IN BIOTECHNOLOGY SUBJECTS - Noris, M; Nurhajarurahmah, St; Darmin, Darmin; Iksan, Muammar; Alkhair, Alkhair; Husnul Khatimah, Nur; Zara Avila, Dea (Journal of Excellence Humanities and Religiosity, 2024)
The purpose of the study was to develop scientific-based E-Modules in biotechnology courses. This type of research is an R&D research with the 4D method. The research sample involved 30 Nutrition students, Muhammadiyah University of Bima. The results showed that the E-Module developed had a high level of feasibility with a percentage ranging from 86. 93% with a very good category. This shows that the developed E-MODUL is suitable for use as teaching material in biotechnology courses. The developed E-MODUL has characteristics that are simple, flexible, interactive, usability, reusable, maintenable, and easily accessible by lecturers and students. The implication is that the developed E-Module can be accessed by students and lecturers of the nutrition study program, bima muhammadiyah university. There is a need for development by involving augmented reality, so that the presentation is based on factual phenomena.